KITD816V mutation in blood for the diagnostic screening of systemic mastocytosis and mast cell activation syndromes. Issue 5 (28th November 2022) - Navarro‐Navarro, Paula; Álvarez‐Twose, Iván; Pérez‐Pons, Alba; Henriques, Ana; Mayado, Andrea; García‐Montero, Andrés C.; Sánchez‐Muñoz, Laura; González‐López, Oscar; Matito, Almudena; Caldas, Carolina; Jara‐Acevedo, María; Orfao, Alberto
Abstract: Background: Current diagnostic algorithms for systemic mastocytosis (SM) rely on the detection of KIT D816V in blood to trigger subsequent bone marrow (BM) investigations. Methods: Here, we correlated the KIT D816V mutational status of paired blood and BM samples from 368 adults diagnosed with mast cell activation syndrome (MCAS) and mastocytosis and determined the potential utility of investigating KIT D816V in genomic DNA from blood‐purified myeloid cell populations to increase diagnostic sensitivity. In a subset of 69 patients, we further evaluated the kinetics of the KIT D816V cell burden during follow‐up and its association with disease outcome. Results: Our results showed a high correlation ( P < .0001) between the KIT D816V mutation burden in blood and BM (74% concordant samples), but with a lower mean of KIT D816V‐mutated cells in blood ( P = .0004) and a high rate of discordant BM + /blood − samples particularly among clonal MCAS (73%) and BM mastocytosis (51%), but also in cutaneous mastocytosis (9%), indolent SM (15%), and well‐differentiated variants of indolent SM (7%). Purification of different compartments of blood‐derived myeloid cells was done in 28 patients who were BM mast cell (MC) + /blood − for KIT D816V, revealing KIT D816V‐mutated eosinophils (56%), basophils (25%), neutrophils (29%), and/or monocytes (31%) in most (61%) patients. Prognostically, the presence of ≥3.5% KIT D816V‐mutated cells ( P < .0001) and an unstable KIT D816V mutation cell burden ( P < .0001) in blood and/or BM were both associated with a significantly shortened progression‐free survival (PFS). Conclusions: These results confirm the high specificity but limited sensitivity of KIT D816V analysis in whole blood for the diagnostic screening of SM and other primary MCAS, which might be overcome by assessing the mutation in blood‐purified myeloid cell populations. Abstract : This study evaluates the utility of KIT D816V mutational status in blood (vs. bone marrow) for the diagnostic screening of SM and MCAS patients, having a high specificity but a limited sensitivity in patients presenting with clonal MCAS without skin lesions. Assessment of KIT D816V in blood‐purified myeloid cell populations increases the diagnostic sensitivity of this mutation in 61% of patients. Further, an unstable (decrease or increase) KIT mutation cell burden during follow‐up is a strong predictor of shortened progression‐free survival in SM.Abbreviations: BM, bone marrow; KITD816V, somatic mutation in codon 816 of the stem cell growth factor receptor gene; MC, mast cell; MCAS, mast cell activation syndromes; No., number; PFS, progression‐free survival; SM, systemic mastocytosis